2000
DOI: 10.1143/jjap.39.4153
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties and Strain Analysis in Paraelectric ZrTiO4Thin Films Deposited by DC Magnetron Sputtering

Abstract: The dielectric constants and dielectric losses of ZrTiO 4 thin films deposited by DC magnetron reactive sputtering were investigated. The paraelectric properties were measured in the 100 kHz range, and compared with an equivalent circuit model. As the deposition temperature increased (up to 600 • C), the dielectric losses (tan δ) decreased (down to 0.017 ± 0.007), while the dielectric constants (ε) were in the range of 35 ± 7. Post annealing at 800 • C in oxygen for 2 h reduced tan δ down to 0.005 ± 0.001, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…The series resistor in this equivalent-circuit model represents the difference (in two test structures) in both the resistance from the electrodes and the contact resistance. 11,12,24) The impedance of the equivalent circuit can be expressed in the following equations:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The series resistor in this equivalent-circuit model represents the difference (in two test structures) in both the resistance from the electrodes and the contact resistance. 11,12,24) The impedance of the equivalent circuit can be expressed in the following equations:…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies were focused on the dielectric properties around the MHz frequency range, leakage current, and optical index of refraction. [11][12][13][14][15][16] However, the dielectric properties of these thin films in the microwave ranges have not been reported yet. Therefore, in this paper, the effects of deposition temperature and incident power density on the dielectric losses and dielectric constants in the microwave range are reported.…”
Section: Introductionmentioning
confidence: 99%
“…The change in the dielectric constants due to the variation in the deposition temperature [5]. Moreover, those the correlation between the micro strain and dielectric loss of ZrTiO4 thin films were studied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, zirconium titanate (ZrTiO 4 ) is a well‐known ceramic material, being suitable for manufacturing electrical and optical devices such as capacitors, piezoelectric sensors, ultrasonic motors, and dielectric devices in microwaves, due to its high permittivity in the microwave frequency . Kim et al showed that the ZrTiO 4 prepared by magnetron sputtering at 600 °C and annealed in an oxygen atmosphere at 800 °C for 2 h exhibited good dielectric properties, which can be sufficient for contacts, electrodes, and dielectric itself, and stray inductance of the contacts and wires . Recently it was reported the superior biocompatibility of TiO 2 –ZrO 2 –ZrTiO 4 nanotubes .…”
Section: Introductionmentioning
confidence: 99%